2021
DOI: 10.5861/ijrsm.2021.m058
|View full text |Cite
|
Sign up to set email alerts
|

Department of Trade and Industry (DTI) IV: A marketing assistance to micro, small, and medium enterprises and its financial impact: Inputs to marketing plan

Abstract: This study determined the level of marketing assistance being provided by the Department of Trade and Industry (DTI) IV-A to micro, small, and medium enterprises (MSMEs) and the level of its financial impact. The descriptive correlational method was utilized, and the respondents were the marketing assisted MSMEs in the CALABARZON region. The researcher used a survey questionnaire and a simple mean and four-point Likert scale, and Pearson product moment correlation was used for its statistical treatment. Conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Buch et al (2012) in their research on Jordan manufacturing SMEs, also agreed with the statement that financial had a positive influence on SMEs internationalization. Moreover, Paterno (2021) suggested that finances had a positive influence on SMEs' internationalization based on their research on Belgian SMEs that pursued foreign direct investments. This statement was also supported by Buch et al (2014) who suggested that financial had a positive influence on SMEs internationalization.…”
Section: Availability Of Resourcesmentioning
confidence: 99%
“…Buch et al (2012) in their research on Jordan manufacturing SMEs, also agreed with the statement that financial had a positive influence on SMEs internationalization. Moreover, Paterno (2021) suggested that finances had a positive influence on SMEs' internationalization based on their research on Belgian SMEs that pursued foreign direct investments. This statement was also supported by Buch et al (2014) who suggested that financial had a positive influence on SMEs internationalization.…”
Section: Availability Of Resourcesmentioning
confidence: 99%